Theories of Personality / Fifth Edition - Ryckman Richard M (Brooks/Cole Publishing Company, 1993)
An Introduction to the Discipline, Personality and the Scientific Outlook, Psychoanalytic and Neoanalytic Perspectives, Freud's Psychoanalytic Theory, Jung's Analytical Psychology, Adler's Individual Psychology, Horney's Social and Cultural Psychoanalysis, Fromm's Humanistic Psychoanalysis, Errikson's Psychoanalytic Ego Psychology, Trait Perspectives, Allport's Trait Theory, Cattell's Structure-Based Systems Theory, Eysenck's Biological Typology, Cognitive Perspectives, Kelly's Theory of Personal Xonstructs, Humanistic and Existential Perspectives, Maslow's Self-Actualization Position, Roger's Person-Centered Theory, May's Existential-Analytic Position, Social-Behavioristic Perspectives, Skinner's Operant Analysis, Rotter's Expectancy-Reinforcement Value Model, Bandura's Social Cognitive Theory, The Role of Personality Theories in Contemporary Personality Psychology, Contributions of Personality Theories to the Discipline.